Can The Configuration of Petrous Bone Pneumatization be a Predictor of Tinnitus? - Abdullah Soydan Mahmutoğlu; İrfan Çelebi (İstanbul Medical Journal, 2018)

(untitled)
Introduction: In this study, we tried to evaluate a possible relationship between petrous bone pneumatization and subjective pulsatile tinnitus (SPT).Methods: The temporal bone computed tomographic (CT) images of 35 patients with SPT admitted to our hospital between October 2013 and May 2014 were evaluated. We formed the control group by a retrospective evaluation of the reconstructed images of the petrous bones derived from the paranasal CT scans of 35 patients free of SPT complaints performed because of chronic sinusitis.Results: Overall, 46 ears of patients with SPT were evaluated. Of these, 13 (28.26%) had petrous bone pneumatization. Of these, 11 of them had increased pneumatization formed of small aircells, whereas two had predominant large aircells between internal carotid artery (ICA) and cochlea. In the control group, 15 (21.42%) of 70 ears had petrous bone pneumatization formed of small air cells. On comparing study and control groups, no significant relationship was found between petrous pneumatization and tinnitus (p>0.05).Conclusion: In our study, we did not find any significant relationship between pneumatization and tinnitus, but we detected two patients with bilateral pneumatization, who had SPT at the side of pneumatization, which mainly consisted of a unibody large air cell; however, the opposite sides, which consisted of multiple small aircells, were free of tinnitus. For these cases, a question arises whether a combination of thin bony lamellas and tiny air cells together causing multiple interfaces resulting in dispersion and reflection, thus reducing the energy of the sound and existence of a unibody large aircell conducting the sound with relatively less distortion, eventually resulting in not amplification but less interference on the sound can be perceived by cochlea as relatively increased conduction of the blood flow and result in SPT. To prove this theory, a study with a large number of cases in resemblance has to be conducted.